DOES ICTS MATTERS FOR CORRUPTION? - Caroline Gratia Sinuraya; Tutik Rachmawati (Asia Pacific Fraud Journal, 2016)
Corruption is a common term used in both private and public sector to understand the misused of resources in order to enriched themselves, unlawfully. Corruption has been endemic in Indonesia starting from the highest peak of government to the grass root level. Some organizations had tried to eradicate corruption with any possible way they could find; law enforcement, behavioural to education approach. However, the use of information, technology and communication or ICTS or known as e-Government in eradicating corruption has been considered a break trough. They believe that by implementing ICTS in several sectors of public services, it could help to eradicate corruption in Indonesia. Local Governments has been using e-budgeting but corruption is still prevalent. ICTS serves as way to reduce corruption rate but it does not eradicate corruption at all. The adoption of ICTS in governmental systems creates an opportunity for the officers and staffs who understand and occupies skills of ICTS (e-literate) and at the same time blocks chances for those who do not understand ICTS. This is called as an up-skilling corruption. This paper will discuss e-administration which is understood as ‘the use of information and communication technologies and in particular the internet, as a tool to establish a better-quality administration. Using a case study of e-administration in Bandung City, this paper will discuss how Bandung City is to implement Online Licensing through BPPT or Badan Pengkajian dan Penerapan Teknologi (The Agency Assesment and Application of Technology) with a consideration that there is a chance for up-skilling corruption. Further, upon the discussion, recommendation on how to implement proper e-administration so that it will achieve its goal to eradicate corruption.